(untitled) (American Journal of Business Management, Economics and Banking, 2023)
The invasion of right to privacy is considered as one of the modern torts in the English law and referred to as the tort of invasion of right to privacy. It is worthbearing in mind that this kind of tort was not known in the previously in the English law، and the defamation action did not give protection to the right to privacy، because it has only protected the reputation، and the law of tort، which is considered as a part of the common law،did only include the duty of confidence or duty of confidentiality،which participated in the presence of the traditional tort called the tort of breach of confidence or breach of confidentiality. as far as the Iraqi law is concerned، The Iraqi constitution of 2005 determined the context of the right to privacy، whereas the Iraqi civil law No. 40 of 1951does not contain any provision determining the context of this right، nor does it provide for act regarded as the violation or invasion of this right.